DOI: 10.1016/s0742-7301(00)19007-3
|View full text |Cite
|
Sign up to set email alerts
|

Compensation in nonprofit organizations

Abstract: Although the nonprofit sector is enormous, we know little about how workers there are compensated. This may be due, in part,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…This is consistent with the institutional rigidity arguments put forth earlier in the paper. According to Hallock (2000), not-for-profits often peg compensation to educational credentials. Thus, unlike for-profits, not-for-profits cannot easily relax institutional constraints that tie compensation to educational qualifications.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the institutional rigidity arguments put forth earlier in the paper. According to Hallock (2000), not-for-profits often peg compensation to educational credentials. Thus, unlike for-profits, not-for-profits cannot easily relax institutional constraints that tie compensation to educational qualifications.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarship regarding nonprofit wages has been largely descriptive (e.g., Hallock, 2000), focused on public charities, and concerned with the differential wages between the for-profit and nonprofit sectors. Nonprofit executive compensation has been demonstrated to have a relationship with organization size, organization type, subsector category, ideology, and level of reliance on public donations (Frumkin & Keating, 2010;Gray & Benson, 2003;Oster, 1998;Twombly & Gantz, 2001;Urban Institute, 2001).…”
Section: The Evolution Of Nonprofit Financial Performance Studiesmentioning
confidence: 99%
“…Regarding NPOs, a number of studies have investigated differences in salary levels between nonprofit and for-profit organizations and also differences in salary levels within the NPO sector Langer, 1989;O'Connell, 1992;Osters, 1998). Previous research has identified determinants on salary levels (Hallock, 2000;Handy & Katz, 1998;Schiff & Weisbrod, 1993).…”
Section: Typology Of Compensation Systemsmentioning
confidence: 99%